Effect of the Polymorphic Variant p.D1472H on the Platelet‐Dependent VWF Activity Assays - Seidizadeh, Omid; Pati, Lismaira; Baronciani, Luciano; Colpani, Paola; Cozzi, Giovanna; Pagliari, Maria Teresa; Novembrino, Cristina; Cairo, Andrea; Pappalardo, Emanuela; Peyvandi, Flora (Haemophilia : the official journal of the World Federation of Hemophilia, 2025)
ABSTRACT Background The von Willebrand factor (VWF) p.D1472H variant has been shown to artificially lower ristocetin cofactor (VWF:RCo) levels because of impaired VWF binding to ristocetin. Understanding the variant's effect on platelet‐dependent VWF activity assays is crucial for avoiding over‐ or misdiagnosis of von Willebrand disease. Aim To determine whether p.D1472H affects the VWF:GPIbR latex immunoassay (LIA). Methods We investigated 150 subjects for VWF:Ag and platelet‐dependent VWF activity using four commercially available assays: VWF:GPIbR LIA, VWF:GPIbR chemiluminescence immunoassay (CLIA), VWF:RCo automated, and VWF:GPIbM LIA. p.D1472H was detected directly using Sanger sequencing or as part of other projects using next‐generation sequencing (NGS). Results A total of 106 subjects were homozygous for aspartic acid [p.D1472H (‐)], 41 heterozygous, and 3 homozygous for histidine [p.D1472H (+)]. Using VWF:RCo, p.D1472H (+) subjects (n = 44) showed a significantly lower median VWF activity/VWF:Ag ratio than p.D1472H (−) subjects (p < 0.0001). No significant difference for this ratio was observed between the two groups when assessed using VWF:GPIbR LIA (p = 0.63). Similarly, no significant difference was observed in the presence or absence of the variant (p = 0.31) for the VWF:GPIbR CLIA. Using VWF:GPIbM, a significant difference (p = 0.00052) was observed between the two median ratios. Conclusions Our results for the first time show that VWF:GPIbR LIA, despite using ristocetin, is not affected by p.D1472H; hence, it offers reliable results to differentiate VWF quantitative from qualitative deficiencies. We further confirmed that VWF:RCo is highly compromised by p.D1472H, while VWF:GPIbR CLIA is unaffected. VWF:GPIbM LIA results were significantly lower in the p.D1472H (+) subjects than those in p.D1472H (−).